EFEKTIVITAS, DAMPAK, DAN KEBERHASILAN TAX AMNESTY DI INDONESIA - Randy Kurnia Permana, SE., M.Ak. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
Indonesia is one of the countries that organizes tax amnesty and is the country with the highest tax amnesty money in the world. Apart from this, many targets set by the government regarding Tax Amnesty have not been achieved. The level of compliance of taxpayers who follow Tax Amnesty is also low, which is still below 5%. The impact of the first tax amnesty is to boost investment rates. Tax Amnesty will attract funds from abroad into the country, a sector that is affected by tax amnesty which is believed to drive economic growth in Indonesia and also creates envy for taxpayers who are already obedient to taxation in Indonesia.